Attitudes towards English language learning and language use among secondary school students / Harjander Kaur a/p Santa Singh - Santa Singh, Harjander Kaur (2014)
at least eleven years of English language education, many Malaysians are still not proficient in the language which is leading to higher education having to offer further English language support, and employers complaining about the level of English language proficiency among graduates. This present study examines to what extent the respondents use English at home and with their peers, to what extent are the respondents motivated to use and learn English and to what extent are the patterns of language use and attitudes related to their proficiency in English. This study comprised a questionnaire distributed to 30, 14 years old respondents from different ethnic groups and different background from a semi-urban secondary school in Malaysia. The questionnaire was designed to obtain information about the respondents’ use of English, their attitudes towards English and their motivation for learning English. Nine respondents, among the 30 were interviewed to obtain in-depth insights on these elements. This study reveals that the respondents generally had a positive attitude towards learning English and were motivated to learn it regardless of their family backgrounds and proficiency levels. The respondents whose parents held professional jobs tended to be more proficient than those whose parents did not.